2018
DOI: 10.1007/s00246-018-1873-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial Variation in Echocardiographic Reference Ranges for Left Chamber Dimensions in Children and Adolescents: A Systematic Review

Abstract: Echocardiography plays a critical role in the assessment of cardiac disease. Important differences in echocardiographically derived cardiac chamber dimensions have been previously highlighted in different population groups in adult studies, but this has not been systematically studied in children, whose body size changes throughout childhood. The aim of this study was to review the distribution of available reference ranges for the left cardiac chamber dimensions in older children and adolescents. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…It has been demonstrated that ethnicity and genetic factors contribute to explain the variability in LA dimensions. A recent systematic review based on 36 studies (only one with data from South America) including 30 607 children and adolescents underlined the importance of using race‐specific reference ranges for left cardiac chamber dimensions, as well as the need for standardizing echocardiographic methods in deriving the reference ranges . Then, the value of developing percentile curves for children and adolescents from the Southern Cone of Latin America results easily comprehensible to adequately interpret LA dimensions and early detect LA enlargement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that ethnicity and genetic factors contribute to explain the variability in LA dimensions. A recent systematic review based on 36 studies (only one with data from South America) including 30 607 children and adolescents underlined the importance of using race‐specific reference ranges for left cardiac chamber dimensions, as well as the need for standardizing echocardiographic methods in deriving the reference ranges . Then, the value of developing percentile curves for children and adolescents from the Southern Cone of Latin America results easily comprehensible to adequately interpret LA dimensions and early detect LA enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the technological advances in cardiovascular imaging, jointly considering accuracy, availability, safety, and versatility, measurement of cardiac structures by 2DE is the preferred modality for the initial evaluation of cardiac structure and function . Moreover, 2DE remains a fundamental tool for evaluation, diagnosis, and decision‐making in children with congenital or acquired heart disease …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations